Effects of amino acid restriction on cell cycle progression and/or differentiation in vitro - ERTUGRUL BILGILI, NAGEHAN (2024)
Nutrient restriction during fetal development is a well-established risk factor for disease in later life. Protein restriction in rodent pregnancy results in offspring with impaired organ structure due to the formation of fewer functional units. It is believed that this is consequent to a slowing of cell cycle progression in progenitor tissues during development. We hypothesised that a similar outcome should be seen in undifferentiated proliferating cells in vitro when exposed to a reduced amino acid (AA) supply. We examined the effect of restricting AA provision on cell cycle progression in differentiable C2C12 myofibroblasts. Cells were cultured in HBSS based medium varying in AA concentrations for up to 48h. Cell cycle progression was assessed using fluorescence-activated cell sorting analysis and differences in gene expression were assessed by RNA sequencing. Transcription profile of genes in myosin heavy chain isoforms and myogenic regulator factor were observed to understand proliferation and differentiation capacity of cells under amino acid restriction. AA restriction significantly reduced cell number (40% at 50%AA and 57% at 20%AA; P <0.001). This was due to a slowing of cell-cycle progression with the transition from G1 to S phase being reduced by ~28% with AA at 50% of control, or (P = 0.01). The effect of AA restriction was only observed in the presence of an adequate glucose concentration. Inhibited cell cycle progression is associated with alterations in the expression of cell cycle regulatory genes and reduced amino supply shifted cell cycle regulation, causing cells to move more slowly through the cell cycle and changing the transition of cells from G1 to the S phase in vitro. Limitation of amino acid supply greatly altered the expression of genes in cholesterol synthesis pathway through all stages of cell cycle and reduced both IGF1 and IGF2 gene expression. Genes specific to muscle proliferation and differentiation also downregulated by LP supply. The data in this thesis showed that relatively modest amino acid restriction imposed on undifferentiated cells in culture impaired proliferation by slowing progression through the cell cycle via stalling cells in the G1.